Meeting Dan Sperber’s Challenge to Searlean Social Ontology (Rivista Italiana di Filosofia Analitica Junior, 2011)
What follows is a brief commentary to Dan Sperber's plenary lecture at ECAP7 "The deconstruction of social unreality". Sperber's main criticism to Searle's socia lontology is that Searle attributes a causal role to mere Cambridge properties (in Sperber'sexample: Jones dies, so the rest of the world gains the Cambridge status of "Jones' survivors"). Sperber then argues that declarations do not create institutional facts causally, criticizes the Serlean theory of recognition/acceptance and put forward his thesis using the concept cognitive causal chains.